2013
DOI: 10.1177/1086296x13504867
|View full text |Cite
|
Sign up to set email alerts
|

A Research Metasynthesis on Digital Video Composing in Classrooms

Abstract: Calls for research documenting outcomes of new literacy practices in school (e.g., Moje, 2009) focus on the need for understanding adolescents' experiences, what they learn about content, about literacy practices, and about their identities and positions in the world. This metasynthesis of findings from 27 qualitative studies of digital video (DV) composing in secondary schools involved 97 teachers and 135 students as focal participants in ethnographic, case, and grounded theory studies. The focus was on the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 37 publications
4
17
0
Order By: Relevance
“…Teachers may also perceive such integration to be incompatible with prescriptive demands placed upon their work, such as conforming to standards or to a test-centric school culture (Siegel, 2012). Miller (2013) concluded the field “urgently needs” further research on how teachers integrate multimodal communication into their instruction (p. 24). Yet, teachers must integrate digital tools and multimodality without neglecting conventional skills assessed on standardized tests (Siegel, 2012).…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…Teachers may also perceive such integration to be incompatible with prescriptive demands placed upon their work, such as conforming to standards or to a test-centric school culture (Siegel, 2012). Miller (2013) concluded the field “urgently needs” further research on how teachers integrate multimodal communication into their instruction (p. 24). Yet, teachers must integrate digital tools and multimodality without neglecting conventional skills assessed on standardized tests (Siegel, 2012).…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…Much of the theory and research on digital literacies teaching in contexts of schooling has been generated by scholars trained in, living, and working in advanced global economies (e.g., Leu et al, 2013;Mills, 2015;New London Group, 1996;Rowsell et al, 2016, Spires et al, 2012. In very broad terms, this scholarship has emphasized the importance of disciplinary problem-based inquiry and digital media production in school as promising approaches for learning digital skills and for developing foundational critical and evaluative dispositions for making media with, and from, digital texts (e.g., Coiro, Castek, & Quinn, 2016;Dwyer, 2016;Miller, 2013;Spires, Kerkhoff, & Graham, 2016;Stornaiuolo & Thomas, 2018). Several studies suggest that projects driven by students' interests and experiences, that invite collaboration, and that incorporate the use of multimodal digital composition and participatory practices can enable exploration of culture and identity, support student agency development, and digital literacies learning concomitantly (e.g., Garcia, Mirra, Morrell, Martinez, & Scorza, 2015;Hughes, 2008;Kafai, Fields, & Searle, 2014;Santoy, 2013).…”
Section: Digital Literacies Teaching and Learningmentioning
confidence: 99%
“…Crippen and Archambault (2012) discussed the importance of integrating technology, such as data mash-ups, into science, technology, engineering and math (STEM) instruction to better support students' understanding of the practical problems that can be addressed through STEM instructional goals. Finally, Miller (2013) found that providing opportunities for secondary students to compose digital videos in response to specific instructional goals resulted in the creation of authentic spaces for learning, increased focus on the dimensions of multimodal design, and collaboration for instructional purposes. The importance of situating technology use within the classroom is further supported by a recent study of fourth-and fifth-grade students that explored the types of digital activities they engaged in both in and out of school.…”
Section: Effective Technology Integration In Instructionmentioning
confidence: 99%